Entrepreneurship and Its Importance for Regional Development in Poland - Iwona LASKOWSKA (Communications of International Proceedings, 2022)
The aim of the paper is to assess the impact of innovative entrepreneurship on the economic growth of regions identified with a voivodeship on the basis of panel data for the years 2010-2020. The analysis uses dynamic econometric models for panel data (GMM estimator). The conducted study indicates that the level of entrepreneurship in Poland is subject to strong regional diversification, with a definite increase in entrepreneurial activity in all voivodeships. The number of innovative enterprises has also increased significantly. Research using regression analysis has confirmed the positive impact of innovative entrepreneurship in the service and industrial sectors on economic growth in the regional dimension. The empirically proven importance of entrepreneurship for economic development indicates that the economic growth prospects of regions are related to the possibilities of creating a good climate that can attract investors and stimulate interest in actions related to investment activity. The results of the research may provide a recommendation for further supporting the development of innovative entrepreneurship by strengthening cooperation between the scientific community, local governments and business in the implementation of innovative solutions.
Keywords: entrepreneurship; innovation; panel models; GMM estimator